Translation of Mangkobar text by Novice Translators and Distribution of Time on Translation Tasks: - - Batubara, Lili Suryani (Bayani, 2024)
This study aimed at finding out how novice translators distribute the time on translation tasks over the phases of translation process while translating mangkobar text from Angkola Language (AL) to Bahasa Indonesia (BI) and from Bahasa Indonesia (BI) to English (EL). The mangkobar text (cultural text) composed of around 221-word long. Five novice translators were involved in this research to translate the mangkobar text with experience and several criteria on translation. Their proficiency level of mother tongue AL (L1) was „very good?, confirmed by ?penasehat adat? in Padang Sidimpuan, score of a paper based TOEFL was more than 503, score of UKBI was more than 578. This study used a qualitative research employing an exploratory case study as a method. The data were collected using integrated problem and decision reports (IPDRs), keyboard logging program (Translog- II), screen recording tool (Camtasia studio 9), and retrospective questionnaire. Two findings were revealed in this study: 1) the novice translators distribute more time on processing in drafting phase whether in translating from AL to BI or BI to EL, 2) they have low capability in managing the time on translation process. It was found that the novice translators took less time when translating from AL to BI since both of languages are their mother tongue and first language so that they understood the source text easily. Meanwhile, it took longer time when translating from BI to EL since they have both linguistic and cultural differences between the SL and the TL.